Diseño de una campaña integral de prevención, mitigación e información ante el consumo de dos de las nuevas drogas emergentes, Tussi y MDMA, al interior de la Universidad Tecnológica de Pereira (2023)
A big problem has been evident regarding the consume of emerging drugs in the interior of our University (UTP) such as 2CB (Tucibi), MDMA, NBOME, LSD DMT, among others. This project seeks to link the advances of the UTP Drugs Observatory and the knowledge, skills and methodologies acquired in the degree in communication and educational computing; mainly related to marketing, advertising, didactics and pedagogy; In this way, a digital marketing strategy is implemented on a website including as a central axis the use of discontinuous texts of the type - flyers - where they mainly talk about the psychosocial risks that entails the consumption of New Psychoactive Substances. In this order of ideas, the generic project is presented, which shows an alternative to prevent and mitigate within the interior of the campus of our University (UTP) supported in this case by the TIC's. Our goal is that the community strengthen its comprehension of the social phenomenon and that, based on this campaign, they take a critical and reflexive position about this situation. The central concept implemented in this degree project is emerging drugs, also known as NPS (New Psychoactive Substances); However, their names vary in some approaches and investigations; but in other instances they are also known as design drugs or recreational drugs ; All three share meaning and meaning; but for the particular case of this work, the concept is implemented Emerging Drugs.